2015
DOI: 10.1002/jcc.23871
|View full text |Cite
|
Sign up to set email alerts
|

Electronic reorganization triggered by electron transfer: The intervalence charge transfer of a Fe3+/Fe2+ bimetallic complex

Abstract: The key role of the molecular orbitals in describing electron transfer processes is put in evidence for the intervalence charge transfer (IVCT) of a synthetic nonheme binuclear mixed-valence Fe(3+)/Fe(2+) compound. The electronic reorganization induced by the IVCT can be quantified by controlling the adaptation of the molecular orbitals to the charge transfer process. We evaluate the transition energy and its polarization effects on the molecular orbitals by means of ab initio calculations. The resulting energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 68 publications
(94 reference statements)
0
17
0
Order By: Relevance
“…Strodel and co-workers developed a nonbonded model Cu(II) model that includes Jahn-Teller effects (56). However, recent investigations showed that the charge transfer effects and electrostatic charges and between the transition metal ion and biospecies dominate the determined biometallic structures (90)(91)(92)(93). Development of force field parameters occurs using nonbonded or bonded models.…”
Section: Introductionmentioning
confidence: 99%
“…Strodel and co-workers developed a nonbonded model Cu(II) model that includes Jahn-Teller effects (56). However, recent investigations showed that the charge transfer effects and electrostatic charges and between the transition metal ion and biospecies dominate the determined biometallic structures (90)(91)(92)(93). Development of force field parameters occurs using nonbonded or bonded models.…”
Section: Introductionmentioning
confidence: 99%
“…From this identification, both the relevant operators and the values of their corresponding interactions can be determined rigorously and univocally. Such a procedure has been used successfully to extract subtle interactions such as electron transfer, [29][30][31][32] Coulomb repulsion, [33] isotropic magnetic coupling, [34][35][36][37][38][39][40] zero-field splitting (ZFS) parameters, [41][42][43][44][45][46][47][48][49][50][51] double exchange interactions, [52][53][54] exchange transfer terms, [30,33,[55][56][57] and three-and four-body terms. [58,59] The NiGa 2 S 4 material is a triangular quasi-two-dimensional lattice constituted of S = 1 (Ni 2+ ) interacting centers.…”
Section: Introductionmentioning
confidence: 99%
“…From this identification, both the relevant operators and the values of their corresponding interactions can be determined rigorously and univocally. Such a procedure has been used successfully to extract subtle interactions such as electron transfer, Coulomb repulsion, isotropic magnetic coupling, zero‐field splitting (ZFS) parameters, double exchange interactions, exchange transfer terms,, , and three‐ and four‐body terms , …”
Section: Introductionmentioning
confidence: 99%
“…This procedure allows us to split the system following a valence bond‐like picture in an orthogonal framework. The method has proven to be extremely efficient not only for the reduction of the number of inactive and virtual MOs in post‐CASSCF treatments in a rational way but also for the analysis of the relevance of chemical regions in energy differences . The procedure is particularly attractive in exchange‐coupling‐constant calculations as one can concentrate the numerical efforts according to the polarizable nature of the different fragments.…”
Section: Methodsmentioning
confidence: 99%